Damming interacts with the flood pulse to alter zooplankton communities in an Amazonian river. (21st March 2019) - Souza, Carla Albuquerque de; Vieira, Ludgero Cardoso Galli; Legendre, Pierre; Carvalho, Priscilla de; Velho, Luiz Felipe Machado; Beisner, Beatrix E.
Abstract: Flow modification of lotic ecosystems is one of the main threats to global freshwater biodiversity. Commonly, and in the river studied here, modification results from hydroelectric dam installation. We evaluated the impacts of damming on zooplankton communities in the Amazonian floodplain of the Madeira River (Porto Velho, Rondônia, Brazil) following construction in 2012 of the run‐of‐river dam of Jirau Hydroelectric Power Plant. Using data sampled between 2009 and 2015, we tested for discontinuities in zooplankton community composition attributable to damming and the naturally occurring flood pulse. The flood pulse remained the main predictor explaining variation in zooplankton community structure even with the installation of the dam on the Madeira River. Despite this, discontinuities for the entire zooplankton community and for the main compositional groups (testate amoebae, rotifers, cladocerans, and copepods) were detected in relation to the dam (pre‐/post‐dam periods), mainly in ebb and low water, and with weaker evidence of dam effects during flood and highwater hydrological periods. A multivariate regression tree explained 9.6% of the variation in zooplankton communities and identified four groups: (1) flood and high‐water periods; (2) low water post‐dam; (3) low water pre‐dam; and (4) ebb hydrological periods. The deviance in each multivariate regression tree node was attributable to variation in eight rotifer, three testate amoeba, and three copepod taxa. Our study demonstrates that the flood pulse, dam construction, and interaction between both of these factors affect zooplankton community structure in the Madeira River. While for many zooplankton community variables, effects occurred mainly during ebb and low‐water periods, some effects were also observed during high water and flood periods. We thus recommend the establishment of a permanent environmental monitoring programme during all hydrological periods in tropical floodplain rivers and the addition of sampling sites downstream from dams. Many rivers in the world are increasingly disrupted by multiple dams, yet little is known of their effects, especially for run‐of‐river dams. Our study identified short‐term impacts of only one run‐of‐river dam on zooplankton communities. More research is needed on the effects of multiple run‐of‐river dams on zooplankton and other biota, especially in tropical floodplain rivers, so that negative effects can be understood and ameliorated.